Are New Forms Necessary for Orthodox Temples? - Bagina, Elena (project baikal, 2014)
Traditionalism of temple architecture gives the society a “link of times” and a necessary sense of deep historical perspective. An architect does not have a right to design religious structures using his own discretion or philosophy. The sphere of innovations in temple architecture is rather limited. It mostly refers to decorations complying with the dominant styles or trends. The volumetric and spatial structure of religious buildings cannot be changed by an architect apart from the religious paradigm.